FERTILITY DYNAMICS OF SEEDS OF FOOD PLANTS GROWING IN THE DESERTS - G.U. Khamroeva; N.Kh. Khalilov (European Journal of Agricultural and Rural Education, 2022)
The article provides information on the study of the dynamics of germination of seeds of desert forage plant varieties. It was found that the seeds of olabuta species have the property of hardness, and their germination can be sharply increased by cold stratification